2012
DOI: 10.7763/ijapm.2012.v2.59
|View full text |Cite
|
Sign up to set email alerts
|

Flow Stress Characteristics of AZ31B Magnesium Alloy Sheet at Elevated Temperatures

Abstract: Abstract-The true stress-strain curves of AZ31B magnesium alloy sheet were obtained by using the uniaxial tensile tests at temperatures ranging from 50℃to 300℃ and initial strain rates ranging from 0.001/s to 0.1/s. The effects of temperature and strain rate on the flow stress were analyzed. The results show that the flow stress decreases and the elongation at fracture increases with increasing temperature and decreasing strain rate, and the formability is improved obviously. Two mathematical models were devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…These small amounts of recrystallized grains were suggested to be the result of an increasing contribution of rotational recrystallization mechanism in the recrystallized grains due to the limited time for diffusion [36,37]. Li et al [38] also found the strain softening due to DRX did not occur in the tensile testing of AZ31B Mg alloy at 50-150 C with strain rates lower than 0.1 s À1 .…”
Section: Microstructural Evolutionmentioning
confidence: 96%
“…These small amounts of recrystallized grains were suggested to be the result of an increasing contribution of rotational recrystallization mechanism in the recrystallized grains due to the limited time for diffusion [36,37]. Li et al [38] also found the strain softening due to DRX did not occur in the tensile testing of AZ31B Mg alloy at 50-150 C with strain rates lower than 0.1 s À1 .…”
Section: Microstructural Evolutionmentioning
confidence: 96%
“…On one side, it may be ascribed to the different potentials used, and on the other side, the applied strain rate plays a critical role. It is well known that the flow stress drops with a deformation rate increase, not only in the Mg system [51,52] but also in other metallic systems such as copper (Cu) [53]. Note that our compression rate (1 × 10 9 s −1 ) is ten times lower than that in the work of Hasan…”
Section: Stress-strain Curvesmentioning
confidence: 62%
“…The exponential model developed by Wen-juan et al [37] was used to define the behavior of AZ31B, while the Johnson-Cook constitutive equations [38] were used for the definition of the stress-strain curves of Ti6Al4V.…”
Section: Finite Element Modeling and Simulation Preparationmentioning
confidence: 99%